An Enriched Environment Enhances Angiogenesis Surrounding the Cingulum in Ischaemic Stroke Rats - Xueyan Shen; Lu Luo; Fei Wang; Kewei Yu; Hongyu Xie; Shan Tian; Gang Liu; Chunrong Bao; Yunhui Fan; Ying Xing; Nianhong Wang; Siyue Li; et al. (Neural Plasticity)
An enriched environment (EE) has been demonstrated to improve functional recovery in animal models of ischaemic stroke through enhancing vascular endothelial growth factor- (VEGF-) mediated neuroprotection accompanied by angiogenesis in the ischaemic hemisphere. Whether EEs also promote VEGF-mediated neuroprotection and angiogenesis in the contralateral hemisphere remains unclear. Here, we explored the effect of EEs on VEGF expression and angiogenesis within the contralateral cerebral cortex in a rat middle cerebral artery occlusion/reperfusion (MCAO/r) model. We assessed the expression levels of platelet endothelial cell adhesion molecule-1 (CD31), VEGF, and endothelial nitric oxide synthase (eNOS) in the whole contralateral cerebral cortex using Western blotting assay but did not find an increase in the expression of CD31, VEGF, or eNOS in MCAO/r rats housed in EEs, which suggested that EEs did not enhance the overall expression of VEGF and eNOS or angiogenesis in the entire contralateral cortex. We further analysed the local effect of EEs by immunohistochemistry and found that in and around the bilateral cingulum in MCAO/r rats housed in EEs, haematopoietic progenitor cell antigen- (CD34-) positive endothelial progenitor cells were significantly increased compared with those of rats housed in standard cages (SCs). Further experiments showed that EEs increased neuronal VEGF expression surrounding the cingulum in MCAO/r rats and robustly upregulated eNOS expression. These results revealed that EEs enhanced angiogenesis, VEGF expression, and activation of the VEGF-eNOS pathway in and/or around the cingulum in MCAO/r rats, which were involved in the functional recovery of MCAO/r rats.